Metode Eklektik dalam Pembelajaran Bahasa Arab: Mengintegrasikan Qawaid wa Tarjamah dan Sam'iyah Basariyah untuk Meningkatkan Kemahiran Berbicara dan Menulis - Hasani, Nur; Manshur, Umar (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
This study aims to explore the implementation of the eclectic method in Arabic language teaching through the integration of Qawaid wa Tarjamah and Sam'iyah wa Bashariyah methods to enhance students' speaking and writing skills. Arabic language teaching at SMP Nurul Jadid reveals that effective learning requires a variety of methods, including the combination of several techniques that can be adjusted to the dynamics occurring in the classroom. Field practice indicates that method changes frequently occur within a single lesson to align with students' responses and needs. This research employs a qualitative descriptive approach. Data were collected through interviews, observations, and documentation, and analyzed using data triangulation techniques. The results of this study show that the application of the eclectic method, integrating the two approaches—Qawaid wa Tarjamah and Sam'iyah wa Bashariyah—positively impacts the improvement of students' speaking and writing skills, as well as their motivation. The eclectic method proved effective in enhancing Arabic language proficiency by providing students with the freedom to manage their own learning process, thereby increasing their sense of responsibility and intrinsic motivation to further develop their Arabic language skills. This study contributes significantly to the development of more effective language teaching methods, particularly within the Language Intensive Program (LIPS) at SMP Nurul Jadid.